OBESITAS DAN PENYAKIT PERIODONTAL - Pujiastuti, Peni (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Obesity rate is increasing from year to year, both men and women in the group and increase the level of obesity is due to changes in lifestyle, especially diet. Obesity plays a major risk factor of chronic diseases, chronic diseases and various forms of oral cancer. Periodontal disease is a chronic inflammation in the tissues supporting the teeth. The purpose of this paper would like to know the relationship of obesity to periodontal disease. Obesity is likely to suffer from diabetes mellitus approximately three times more than that is not obese. The main complications of diabetes mellitus is periodontal disease. People who are obese have a possibility of periodontal disease in the oral cavity. The conclusion is an association between obesity and periodontal disease occur in the oral cavity.